STEM-based flipped classroom: Improve students’ critical thinking skills and biological literacy in animalia material - Sekar Darmastuti; Hanum Isfaeni; Ratna Komala (JPBI (Jurnal Pendidikan Biologi Indonesia), 2025)
Students are required to develop essential 21st-century skills, such as critical thinking and biological literacy, to effectively navigate challenges in the globalization era. It is known that the results of PISA 2022 and several studies show that these skills in students are still very low. However, traditional learning models often fail to cultivate these competencies, necessitating the implementation of innovative instructional approaches. This study investigates the impact of the STEM-based flipped classroom model on enhancing students' critical thinking skills and biological literacy. A quasi-experimental research design was employed, involving 120 students from grade VII of junior high school. The experimental group received instruction through the STEM-based flipped classroom approach, while the control group followed a traditional learning model. Learning activities were carried out for eight lesson hours where one lesson hour lasted 40 minutes.  Students' critical thinking skills were assessed using 11 reasoned multiple-choice questions, and biological literacy was measured through 7 reasoned multiple-choice questions. Data analysis was conducted using Multivariate Analysis of Variance (MANOVA). The results of Pillai's Trace, Wilk’s Lambda, Hotelling’s Trace, and Roy’s Largest Root tests indicated a significant effect (p < 0.001, α = 0.05), confirming that the STEM-based flipped classroom model substantially enhances students' critical thinking and biological literacy. These findings suggest that incorporating STEM-based flipped classroom strategies can effectively improve students’ critical thinking and biological literacy, supporting more engaging and meaningful learning experiences. Educators and policymakers should consider adopting this model to better equip students with the competencies needed in the 21st century.